Hand Hygiene Sound Alert: it is a Good Tool to Improve Compliance? - Andre Luiz Alvim; Bráulio Couto (Universidade de Santa Cruz do Sul, 2019)
Background and Objectives: To investigate whether or not it is possible to use a Sound Alert as a tool to improve Hand Hygiene (HH) compliance. Material and methods: This is a pilot study from an Internal Medicine Unit with 16 beds at a Private Hospital in Belo Horizonte, Minas Gerais, Brazil. The Sound Alert is composed by a bell MP3 wireless with micro SD 128MB as its memory card. Handwash compliance was indirectly measured by two indicators: a) monthly volume of alcohol preparation for hands used (mL) for each patient-day; b) monthly volume of soap preparation for hands used (mL) for each patientday. Results: In the pilot study period, the monthly volume of alcohol preparation for hands increased to 26 mL per patient-day (r2 = 0.99; p